Crucial role of the cGAS N terminus in mediating flowable and functional cGAS–DNA condensate formation via DNA interactions - Zhelin Jiang; Fan Shi; Juan Li; Rui Liu; Jinhua Zhou; Zhensheng Zhong; Chaowei Shi; Mingming Ma; ShengQi Xiang; Daxing Gao (Proceedings of the National Academy of Sciences, 2025)
The DNA-sensing protein cGAS plays a pivotal role in the innate immune response and pathogenesis of various diseases. DNA triggers liquid–liquid phase separation (LLPS) and enhances the enzymatic activity of cGAS. However, the regulatory mechanisms of the disordered N terminus remain unclear. Here, we showed that cGAS Nterm , the N-terminal intrinsic disordered region (IDR) of cGAS, modulates the material properties, specifically the flowability, of the condensed phase of cGAS and is required for full enzymatic activity. Full-length cGAS and cGAS Nterm form liquid droplets in the presence of DNA, while the cGAS catalytic domain forms gel-like solid aggregates with compromised enzymatic activity. Multiple key amino acids responsible for the cGAS Nterm –DNA interaction were identified by NMR spectroscopy as well as other biophysical methods and proven to be critical for the functional LLPS of cGAS both in vitro and in vivo. Interestingly, cGAS Nterm acts in trans to transform the solid aggregates of the cGAS catalytic domain into liquid droplets, subsequently restoring its enzymatic activity. Together, our findings highlight the importance of the IDR of cGAS in LLPS upon DNA stimulation and, more importantly, in modulating the fluidity and permeability of the droplets formed by full-length cGAS, which is crucial for its intact enzymatic activity.